2010
DOI: 10.21273/hortsci.45.10.1529
|View full text |Cite
|
Sign up to set email alerts
|

Landscape Coefficients for Single- and Mixed-species Landscapes

Abstract: Urban landscape irrigation is becoming increasingly important from a resource management point of view. Significant water use savings may be achieved if landscape irrigation is based on reference evapotranspiration (ETo). This study measured landscape crop coefficients (KL) for landscapes that are comprised of different vegetation types and irrigation water quality differences affecting KL. The KL was determined from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 21 publications
1
24
0
Order By: Relevance
“…Park et al (2005) documented that the irrigation requirements for an ornamental mixed-species Florida landscape increased over time and used more water than a St. Augustinegrass turf. In Texas, Pannkuk et al (2010) showed that crop coeffi cients for water use were similar among mowed St. Augustinegrass turf, unmowed native prairie grasses [Schizachyrium scoparium (Michx.) Nash and Muhlenbergia capillaries (Lam.)…”
Section: Environmental and Social Issues Water Consumptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Park et al (2005) documented that the irrigation requirements for an ornamental mixed-species Florida landscape increased over time and used more water than a St. Augustinegrass turf. In Texas, Pannkuk et al (2010) showed that crop coeffi cients for water use were similar among mowed St. Augustinegrass turf, unmowed native prairie grasses [Schizachyrium scoparium (Michx.) Nash and Muhlenbergia capillaries (Lam.)…”
Section: Environmental and Social Issues Water Consumptionmentioning
confidence: 99%
“…A paucity of data exist for determining relative water use by turf compared with other landscape plants, particularly outside of arid climates. Minimizing irrigation can conserve water because at least some turfgrasses display luxury consumption of water, a characteristic that may also extend to some native grasses (Kneebone and Pepper, 1984;Pannkuk et al, 2010). Defi cit irrigation, which applies less water than the estimated loss by ET, can provide suitable quality while conserving signifi cant amounts of water and may reduce mowing needs (Fu et al, 2007).…”
Section: Environmental and Social Issues Water Consumptionmentioning
confidence: 99%
“…A typical approach estimates water demand as a fractional proportion of ET ref . The proportion is estimated using adjustment factors to account for species differences in water demand as well as a range of other processes and factors, such as microclimate, soil cover, and the stage of plant growth that potentially modify water flux from the landscape (Grabow et al, 2013;Pannkuk et al, 2010;Radwan et al, 2010). Although earlier approaches often included a large number of adjustment factors, more recent approaches such as the Simplified Landscape Irrigation Demand Estimator (SLIDE) use only a small number of plant factors to estimate water demand (Kjelgren, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Improvements to this approach are certainly needed, particularly in the area of determining empirically based water-loss coefficients (i.e. Plant Factors) for urban tree and woody vegetation (Pannuk et al, 2010). Accurate measurements of under-canopy turf grass are difficult to obtain, but could improve confidence model results.…”
Section: Discussionmentioning
confidence: 99%